Uptake and Pathways in introducing the Vegetable Crop Capsicum by KVK Khordha, Odisha - Dash, AK; Ananth, PN; Singh, S; Jayasankar, P (Journal of Agricultural Extension Management, 2018)
This paper explains about uptakes and pathways of introducing a new vegetable crop capsicum in Khordha district of Odisha by Krishi Vigyan Kendra (KVK), Khordha. The crop was introduced in 2011 through different extension methods and today more than 550 farmers have adopted this crop replacing chillies. The on-farm trial results indicated that the net income was higher with an increase in yield of 170.8 - 215.1 per cent by adopting capsicum in open field condition compared to farmers’ practice of cultivating green chilli. It was also observed that there was a reduction in yield and quality of capsicum grown during spring-summer in open-field condition. The technology trialed was planting of capsicum and maize in the ratio 4:1 by sowing of maize 45 days after transplanting capsicum. The KVK conducted a trial on intercropping of capsicum with maize. For any crop to be established in the district there is a requirement of employing different extension methods for larger adoption. In this case different extension methods viz., individual, group and mass media were employed for faster reach of this crop. On-farm trials, front-line demonstrations, technology week, farmer-scientist interactions, field days, exhibitions and trainings were the specific extension methods. During the period all possible ways for larger adoption of capsicum were undertaken by the KVK. The success points in introducing this crop is the availability of capsicum seeds with all input dealers and high market demand. KVK is still helping farmers in providing advisory services for increasing the area under capsicum and also for higher production.